IMPLEMENTASI APLIKASI E-COURT DALAM MEWUJUDKAN PELAYANAN PUBLIK YANG BAIK DI PENGADILAN NEGERI KOTA MALANG (Jurnal Teknologi dan Komunikasi Pemerintahan, 2020)
All the arrangements of human life are connected with the internet network that is so massive due to an industrial revolution 4.0. The development of existing technology has an impact on government service systems, namely the service approach to the community. If the service is associated with technological development, it will make the service process effective if the government can allocate it through changes in existing technology properly and correctly. E-Court is an instrument in court as a form of service to the community in terms of online case registration, online payment, online summons, and online trial. Prior to the application of the E-Court, the community tended to experience difficulties in carrying out court activities because the community had to come to the place of court before which would take a lot of time and money, this made the lack of efficiency and effectiveness of services in the registration and trial process. , seeing the difficulties of this society, an E-Court application was launched based on Supreme Court regulations that are useful to facilitate the public in conducting court-based technology activities that save time and excessive costs in order to realize the ideals in efficient and effective public services. This study aims to determine the implementation of e-court applications in services in the Malang District Court. This type of research used in this research is qualitative research with a literature study approach. Keyword : E-Court, Implementation and Public Service